LEXICAL DENSITY OF READING TEXT IN ENGLISH TEXTBOOK FOR GRADE XI SENIOR HIGH SCHOOL - Gita Astria Br Keliat; Neni Afrida Sari Harahap (Universitas Negeri Medan, 2022)
This study deals with the lexical density especially the lexical items of English reading texts in the textbook for senior high school. The objectives of the study are to find out the level difficulties of lexical density used in reading text of English textbook and the reason why is level difficulties of lexical density used the way it is in reading text of English textbook. This study was conducted by descriptive method with qualitative approach. The data of this research were the English reading texts of of Bahasa Inggris textbook for grade XI senior high school published by Kementrian Pendidikan dan Kebudayaan Republik Indonesia. The result of the analysis showed that: (1) The level difficulties of lexical density that used in reading text of English textbook is medium lexical density. (2) The lexical density of narrative text entitled The Enchanted Fish have 401 content words and 581 grammatical function with total percentage of lexical density 40.83%, the lexical density of descriptive text entitled Cheetahs have 162 content words and 137 grammatical function with total percentage of lexical density 54.18%, and the lexical density of explanation text entitled Earthquakes have 307 content words and 226 grammatical function with total percentage of lexical density 57.59%. Keywords: Lexical Density, English Reading Texts